Smart Systems: Innovations in Computing Proceedings of SSIC 2021 - Somani, Arun K.; Mundra, Ankit; Doss, Robin; Bhattacharya, Subhajit (Smart Innovation, Systems and Technologies, 2022)
XXVIII, 645 p. 300 illus., 219 illus. in color.